Analisa Penggunaan Forward Contract Hedging pada Nilai Ekspor Barang Ekonomi Provinsi Sumatera Utara - Hernawaty Hernawaty; Heriyati Chrisna; Junawan Junawan (Jurnal AKMAMI (Akuntansi Manajemen Ekonomi), 2020)
This study aims to determine the benefits of using forward contract hedging on the export value of economic goods in North Sumatra Province 2018-2019. This research is quantitative descriptive. The object of research used is the exchange rate difference from receivables from export transactions of economic goods of North Sumatra Province in 2018-2019. The data source used is secondary data obtained from the official website of BPS North Sumatra Province (sumut.bps.go.id) and Bank Indonesia (www.bi.go.id). The data analysis technique uses descriptive techniques by describing the stages of the forward contract systematically. The formula used in calculating the forward contract is Eiteman's formula and Jeff Madura's formula. The results show that forward contract hedging is more effective in 2019 (when the Rupiah exchange rate against the USD is more stable) than in 2018 (when the Rupiah exchange rate against the USD tends to fluctuate in an extreme manner)